Chimeric FLS2 receptors reveal the basis for differential flagellin perception in arabidopsis and tomato - Mueller, Katharina; Bittel, Pascal; Chinchilla, Delphine; Jehle, Anna K.; Albert, Markus; Boller, Thomas; Felix, Georg (The Plant Cell, 2012)
The flagellin receptor of Arabidopsis thaliana, At-FLAGELLIN SENSING2 (FLS2), has become a model for mechanistic and functional studies on plant immune receptors. Here, we started out with a comparison of At-FLS2 and the orthologous tomato (Solanum lycopersicum) receptor Sl-FLS2. Both receptors specifically responded to picomolar concentrations of the genuine flg22 ligand but proved insensitive to >106-fold higher concentrations of CLV3 peptides that have recently been reported as a second type of ligand for At-FLS2. At-FLS2 and Sl-FLS2 exhibit species-specific differences in the recognition of shortened or sequence-modified flg22 ligands. To map the sites responsible for these species-specific traits on the FLS2 receptors, we performed domain swaps, substituting subsets of the 28 leucine-rich repeats (LRRs) in At-FLS2 with the corresponding LRRs from Sl-FLS2. We found that the LRRs 7 to 10 of Sl-FLS2 determine the high affinity of Sl-FLS2 for the core part RINSAKDD of flg22. In addition, we discovered importance of the LRRs 19 to 24 for the responsiveness to C-terminally modified flagellin peptides. These results indicate that ligand perception in FLS2 is a complex molecular process that involves LRRs from both the outermost and innermost LRRs of the FLS2 ectodomain. © 2012 American Society of Plant Biologists. All rights reserved.
CRIS-Team Scopus Importer:2020-03-09